KEMAMPUAN GURU DALAM MEMBUAT SOAL HOTS DALAM UJIAN TENGAH SEMESTER - Nenny Herawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Teachers are an essential key in improving the quality of education. One of the characteristics of good quality education is creating a good learning process, starting from planning, implementation, and evaluation. In line with this, the teachers’ ability to evaluate students is needed, one of which is the HOTS question. The HOTS (Higher Order Thinking Skill) question refers to an instrument used to measure higher-order thinking skills, namely the ability to remember and restate or refer without processing. The research used was School Action Research (PTS) using the Kemmis and Mc. Taggart. This research was conducted at SD Negeri 023 Semoga Jaya. The subjects of this research were eight teachers. Two cycles showed an increase in the results of the performance indicator assessment. The average obtained in the first cycle was <75, while in the second cycle, the average obtained after more intense actions was >75. This result was very satisfying because the teachers understood how to make HOTS questions as learning objectives in the Mid-Semester Exam.